2020
DOI: 10.1515/cclm-2019-1139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EGFR mutation status in malignant pleural effusion and plasma from patients with advanced lung adenocarcinoma

Abstract: BackgroundCell-free DNA (cfDNA) is emerging as a surrogate sample type for mutation analyses. We investigated the suitability of malignant pleural effusion (MPE) and plasma as a biomaterial for analyzing epidermal growth factor receptor (EGFR) mutation by peptide nucleic acid (PNA) clamping-assisted fluorescence melting curve (PANAMutyper™) analysis.MethodsMatched tissue, MPE cell block (MPE-CB), MPE supernatant, and plasma samples were collected from patients with advanced lung adenocarcinoma who had a MPE at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…used tissue as a standard and reported sensitivities of 63.6% in supernatants and 81.8% in cell blocks ( 18 ). Similar results have also been reported in multiple other studies ( 10 , 11 , 19 – 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…used tissue as a standard and reported sensitivities of 63.6% in supernatants and 81.8% in cell blocks ( 18 ). Similar results have also been reported in multiple other studies ( 10 , 11 , 19 – 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…Improved ctDNA detection rates have been observed in cfDNA from non-blood sources compared to blood [ 29 ], with the exception of saliva [ 35 ] and sputum [ 17 , 38 ]. This has been repeatedly demonstrated in pleural effusions secondary to lung cancer, with an increased sensitivity to EGFR mutations in malignant pleural effusions over plasma, as well as over cell pellets from the effusions [ 31 , 32 , 33 , 36 ]. Furthermore, in two independent cohorts of lung adenocarcinoma patients, higher ctDNA abundance was seen in other body fluids, including ascites, pericardial effusions, and CSF, compared to blood plasma [ 39 , 40 ].…”
Section: Reliable Molecular Profiling Of Diseasementioning
confidence: 87%
“…In two case studies of recurrent medulloblastoma, where driver mutations were found to differ between the initial and recurrent disease, cfDNA from CSF was found to accurately detect the changes [ 30 ]. Similarly, cfDNA from pleural effusions has been found to correspond to matched tumour tissue [ 31 , 32 ]. Among 29 patients with lung cancer, 93% of the driver mutations identified in tumour tissue were similarly detected in the cfDNA from pleural effusions [ 33 ].…”
Section: Reliable Molecular Profiling Of Diseasementioning
confidence: 99%